2006
DOI: 10.1128/jvi.00664-06
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Full-Length Semliki Forest Virus Replicon by Retrovirus Particles

Abstract: Conciliating biosafety with efficient gene transfer remains a constant concern in the development of retroviral vectors. Semliki Forest virus (SFV) replicons allow important retroviral vector production with interesting features. It is noteworthy that retroviruses have the ability to package ⌿ ؉ and, to some extent, ⌿ ؊ cellular RNAs. Therefore, it was important to study the retroviral transfer of highly abundant SFV genomes expressing retroviral proteins. Here, we show that full-length SFV-vector replicons, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The major difference between the study by Piver and co-workers 34 and our current study is that they adopted an SFV-based vector containing a non-functional internal 26S promoter, which should lead to the exclusive production of full-length SFV genomic RNA 49 and a reporter gene under the transcriptional control of the SFV replicase. In contrast, our system is characterized by the SFV replicase, which regulates transcription of the entire cis-acting element of the lentiviral component, that is the HIV-1 vector unit, and by the presence of a wildtype 26S subgenomic promoter.…”
Section: Sfv/hiv Hybrid Vectors C Del Vecchio Et Almentioning
confidence: 88%
See 4 more Smart Citations
“…The major difference between the study by Piver and co-workers 34 and our current study is that they adopted an SFV-based vector containing a non-functional internal 26S promoter, which should lead to the exclusive production of full-length SFV genomic RNA 49 and a reporter gene under the transcriptional control of the SFV replicase. In contrast, our system is characterized by the SFV replicase, which regulates transcription of the entire cis-acting element of the lentiviral component, that is the HIV-1 vector unit, and by the presence of a wildtype 26S subgenomic promoter.…”
Section: Sfv/hiv Hybrid Vectors C Del Vecchio Et Almentioning
confidence: 88%
“…Indeed, the use of SFVderived vectors to produce recombinant retroviral particles has been proposed. [30][31][32][33] However, despite the attractive features, this approach has shown that SFV replicons could be packaged within the recombinant particles, 34,41 rendering it unsuitable in gene therapy application for safety reasons. The purpose of this study was to clarify this issue by adopting an SFV/HIV hybrid system for the expression of the HIV-1 vector elements under the transcriptional control of the SFV replicase and for the production of transducing pseudotyped lentiviral particles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations